The policy of Malaysian government to block global terorism movement / Mohd Khairi Ghazli - Ghazli, Mohd Khairi (2018)
This research aims to explain the policy of Malaysian government to block global terrorism movement. The background of the Malaysian government to make a policy to block the global terrorist movement cause emergence of ISIS (Islamic State of Iraq and Syiria) as a global terrorist movement. ISIS becomes as new threats that threaten the internal security of Malaysia and globally. ISIS emergence as a global terrorist movement makes the Malaysian government take decisive steps to prevent the effects of ISIS entry into the country. The policy of Malaysian government has created a laws of terrorism prevention called POTA (Prevention of Terrorism Act). POTA is a policy that is generated by the Counterterrorism namely an attempt to fight or prevent acts of terrorism in a country that is done through various ways one of them is to make acts like POTA and have international cooperation.